When sng meets acupuncture -- a paradigm-shift biomarker for translational research - Wei-Zen Sun; Chih-Cheng Chen; Jaung-Geng Lin (Journal of Traditional and Complementary Medicine)
The sensation of sng (pronounced/səŋ/, the Romanization form of 痠or soreness in Taiwanese Southern Min) associated with de qi, a composite of unique sensations, is a novel phenotype for acupoint stimulation. It is perceived by test participants but also by experienced practitioners as a sensation of “taking the bait” (by fish when fishing), a characteristic heavy and tight sensation from the needle. Here, we propose that sng is a powerful biomarker for de qi associated with successful manual acupuncture. Sngception (sng-ception), a specific somatosensory function of acid-sensation or tether-mode mechano-sensation, may serve as the ideal molecular and physiological link between sng perception and needle manipulation (e.g., lifting, thrusting, and twisting). To explain how manual acupuncture can induce de qi, we constructed a hypothetical model of manual needling-driven sngception. In acupoints (e.g., ST36), an acupuncture needle can easily stick to extracellular matrix (ECM) proteins (e.g., fibronectin and laminin). While the acupuncture needle is manually twisted, it mingles with ECM and delivers a pulling force to ECM-tethered mechanically sensitive ion channels (e.g., acid-sensing ion channels) on somatosensory nerves to induce sngception. The concept of sng and sngception represents an emerging field for research into the peripheral mechanisms of acupuncture.